On the development of modular polyurethane-based bioelastomers for rapid hemostasis and wound healing. (9th March 2023) - Guo, Wanxin; Zhao, Binan; Shafiq, Muhammad; Yu, Xiao; Shen, Yihong; Cui, Jie; Chen, Yujie; Cai, Pengfei; Yuan, Zhengchao; EL-Newehy, Mohamed; EL-Hamshary, Hany; Morsi, Yosry; et al.
Abstract: Massive hemorrhage may be detrimental to the patients, which necessitates the advent of new materials with high hemostatic efficiency and good biocompatibility. The objective of this research was to screen for the effect of the different types of bio-elastomers as hemostatic dressings. 3D loose nanofiber sponges were prepared; PU-TA/Gel showed promising potential. Polyurethane (PU) was synthesized and electrospun to afford porous sponges, which were crosslinked with glutaraldehyde (GA). FTIR and 1 H-NMR evidenced the successful synthesis of PU. The prepared PU-TA/Gel sponge had the highest porosity and water absorption ratio. Besides, PU-TA/Gel sponges exhibited cytocompatibility, negligible hemolysis and the shortest clotting time. PU-TA/Gel sponge rapidly induced stable blood clots with shorter hemostasis time and less bleeding volume in a liver injury model in rats. Intriguingly, PU-TA/Gel sponges also induced good skin regeneration in a full-thickness excisional defect model as revealed by the histological analysis. These results showed that the PU-TA/Gel-based sponges may offer an alternative platform for hemostasis and wound healing. Graphical Abstract: